A Case Study In Contract Breach Lawsuits, Decision Of The Bantul Religious Court Number: 0463/Pdt.G/2011/Pa.Btl - Fathor Razi (Faculty of Law, Muhammadiyah University of Surabaya, 2025)
This study aims to examine the judge's decision at the Bantul Religious Court in a contract violation case number 0463/Pdt.G/2011/PA.Btl. This study is descriptive-analytical in nature, revealing key findings, which are then analyzed through the research object. This approach uses a case study method through interviews with judges. The main focus of the case study approach is ratio decidendi. The data obtained was then analyzed using a descriptive-analytical approach related to the main issues in the contract breach lawsuit. Based on the results of the investigation, the object of dispute in this case was ambiguity in the terms of the contract between the two parties, which the judge explained as a mudarabah muthlaqah contract. The judge's considerations refer to the Qur'an, KHES, Kep-Men-Kop dan UKM Number 91/Kep/M.KUKM/IX/2004, and the Technical Guidelines for Administration and Religious Courts. The judge's scientific approach was obtained through a master's program in law and socialization related to Law Number 3 of 2006. In deciding the breach of contract case, the judge used collective ijtihad amid the lack of material legal sources that have not been fully regulated in a rigid and concrete manner.